2020
DOI: 10.17511/jopm.2020.i01.01
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the spectrum of histomorphological patterns on endoscopic biopsy in patients with upper gastrointestinal tract disorders

Abstract: Introduction: The upper gastrointestinal tract (UGT) disorders are more common complaints in clinical practice and have got high degree of mortality and morbidity. Many different types of lesions can affect the upper gastrointestinal tract and can be classified as congenital anomalies, infections, inflammation and neoplastic lesions. Material and Methods: A total of 152 cases of upper gastrointestinal tract biopsies are included in this study, out of which 113 cases were gastric biopsies, 22 cases were esophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…depicts the histopathological spectrum observed in upper GIT biopsies in different studies. In the present study, non-neoplastic lesions outnumbered the neoplastic ones, which is in concordance with various studies [11][12][13]15,18. However, the studies of Bhargavi et al,Nazrin et al, and Dutta et al, showed neoplastic lesions to be the…”
supporting
confidence: 93%
See 2 more Smart Citations
“…depicts the histopathological spectrum observed in upper GIT biopsies in different studies. In the present study, non-neoplastic lesions outnumbered the neoplastic ones, which is in concordance with various studies [11][12][13]15,18. However, the studies of Bhargavi et al,Nazrin et al, and Dutta et al, showed neoplastic lesions to be the…”
supporting
confidence: 93%
“…H. pylori gastritis was commonly noted lesion in various studies. 10,13,15,16,18 Varied frequencies of H. pylori gastritis might be due to variables such as geographic area, age, race, ethnicity, and socioeconomic status. Rates appear to be higher in developing than in developed countries and they seem to be decreasing with improvements in hygiene practices and due to the availability of good antibiotics and antacids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Male to Female ratio was 1.39: 1, which was similar to the study done by Shennak MM et al 9 and Rashmi K et al 4 reflecting the fact that males could be exposed to more risk factors than females. In these studies, the men outnumbered women due to more prevalence of smoking, alcoholism, and stressful life similar to studies done by Paymaster et al 10 Among 21 esophageal biopsies, 18 (85%) were non neoplastic and 3 (15%) were neoplastic, the most common non neoplastic lesion was Esophagitis seen in 10 out of 21 cases also seen in Theresa JM et al 11 studies which followed barrettes esophagus and dysplasia. In the present study 100% concordance was seen in cases of esophagitis and barrettes esophagus on both endoscopic and histopathological diagnosis.…”
Section: Discussionsupporting
confidence: 68%
“…Endoscopy was first used in 1986; the upper gastrointestinal flexible fiber optic endoscope revolutionized the way in which GIT abnormalities could be diagnosed [13]. Endoscopic biopsy examination followed by histologic assessment is a convenient procedure and the current gold standard for accurate objective assessment of patients with symptoms of upper GIT.…”
Section: Introductionmentioning
confidence: 99%